Effect of staw application on rice yields and nutrient availability on an alkaline and a pHneutral soil in a Sahelian irrigation scheme - Asten, Piet J.A. van; Bodegom, P.M. van; Mulder, L.; Kropff, Martin (Springer, 2005)
Like elsewhere in the Sahel, actual rice yields (3–5 t ha−1) are far below yield potential (±8 t ha−1) in an irrigation scheme in central southern Mauritania. Earlier studies showed that yields are especially low on alkaline soils due to N and P deficiency. We investigated the potential of rice straw application as a mean to improve yields and fertilizer efficiency on an alkaline soil (pH 8.2) and a pH-neutral soil (pH 6.2). Application of 5 t straw ha−1 increased yields by 1.1 t ha−1 on average, independent of soil type and fertilizer dose. Contrary to our study, similar studies in Asia showed little short-term effects of straw on yield and N uptake. Straw application improved N availability, but not P availability. The improved N availability was attributed to N mineralized from the straw, from increased mineralization of soil organic matter (SOM) with a low C:N ratio (< 7.2) and from increased mineral fertilizer N (urea) recovery efficiency. We deduced that improved N fertilizer recovery upon straw application was due to reduced nitrification–denitrification losses. On the alkaline soil, volatilization was important, but that process seemed unaffected by straw application. We hypothesize that the positive effects of straw application at our study site are due to low soil C content (< 43 g kg−1) and low C:N ratio compared to most lowland rice soils in Asia.